Renal Function at Two Years in Liver Transplant Patients Receiving Everolimus: Results of a Randomized, Multicenter Study. Issue 7 (28th May 2013) - Saliba, F.; De Simone, P.; Nevens, F.; De Carlis, L.; Metselaar, H. J.; Beckebaum, S.; Jonas, S.; Sudan, D.; Fischer, L.; Duvoux, C.; Chavin, K. D.; Koneru, B.; et al.
Abstract In a 24‐month prospective, randomized, multicenter, open‐label study, de novo liver transplant patients were randomized at 30 days to everolimus (EVR) + Reduced tacrolimus (TAC; n = 245), TAC Control (n = 243) or TAC Elimination (n = 231). Randomization to TAC Elimination was stopped prematurely due to a significantly higher rate of treated biopsy‐proven acute rejection (tBPAR). The incidence of the primary efficacy endpoint, composite efficacy failure rate of tBPAR, graft loss or death postrandomization was similar with EVR + Reduced TAC (10.3%) or TAC Control (12.5%) at month 24 (difference −2.2%, 97.5% confidence interval [CI] −8.8%, 4.4%). BPAR was less frequent in the EVR + Reduced TAC group (6.1% vs. 13.3% in TAC Control, p = 0.010). Adjusted change in estimated glomerular filtration rate (eGFR) from randomization to month 24 was superior with EVR + Reduced TAC versus TAC Control: difference 6.7 mL/min/1.73 m2 (97.5% CI 1.9, 11.4 mL/min/1.73 m2, p = 0.002). Among patients who remained on treatment, mean (SD) eGFR at month 24 was 77.6 (26.5) mL/min/1.73 m2 in the EVR + Reduced TAC group and 66.1 (19.3) mL/min/1.73 m2 in the TAC Control group (p < 0.001). Study medication was discontinued due to adverse events in 28.6% of EVR + Reduced TAC and 18.2% of TAC Control patients. Early introduction of everolimus with reduced‐exposure tacrolimus at 1 month after liver transplantation provided a significant and clinically relevant benefit for renal function at 2 years posttransplant.